Edgework, Fun, and Identification in a Recreational Subculture: Street BMX Riders - Scott, Shane; Austin, D. Mark (Qualitative Sociology Review, 2016)
The sociological study of risk-taking behavior is a relatively recent development. Lyng (1990) and others have developed the field of edgework, or the “sociology of risk-taking.” In this study, we examine a group of edgeworkers to understand the role of fun and identity in a group of BMX “freestyle” bicycle riders and conclude that these riders reject rational reasons, in the sense of the term envisioned by Weber, for riding in favor of choosing an activity that they report as fun, which leads to feelings such as self-actualization and fulfillment. Additionally, they are not concerned that others, outside of the subculture, recognize their status as participants, further suggesting that rationality played little into the calculation used to define success by this group.